Graduate and Student Attitudes Towards Effective Music Education at the Academy of Music - Daucianskaite Agne (European Scientific Journal, ESJ, 2019)
This article presents a qualitative study which aimed to explore and describe effective music education through the experience-based opinions of graduates and students of the Academy of Music. The research questions for the empirical research were: How is effective music education described by students/graduates who continuously practice and permanently learn instrumental music? How do they see the role of the teacher as a component in effective music education? The sample consisted of 14 research participants, 7 of whom were graduates and 7 final (4th) year students. In findings, discussion and conclusions these two subgroups are not divided and compared, as qualitative research does not aim to compare, but rather seeks to provide a deep summary (not generalized) description of the phenomenon. Data collection applied semi-structured interviews and the data analysis was performed using thematic analysis. Findings revealed that students related effective music education primarily to a music teacher’s personality traits and professional competence. Yet the music teacher’s role is seen as broader by graduates/students: a music teacher is important as an equal collaborator in discussions, performances and learning; students need to reflect, they need to experience support and respect for their own decisions in their own music career. In conclusion, it is important to note that effective music education requires from the teacher both a good understanding of music or the ability to master the necessary techniques, and the ability to convey musical traits to the students.